2001
DOI: 10.1590/s0041-87812001000600002
|View full text |Cite
|
Sign up to set email alerts
|

Conization, frozen section examination, and planned hysterectomy in the treatment of high-grade cervical intraepithelial neoplasia

Abstract: In high-grade cervical intraepithelial neoplasia, frozen section examination can provide immediate and precise evaluation of the cone margin status in high-grade cervical intraepithelial neoplasia. It can identify frank invasion and permit adequate treatment in a one-stage procedure. In early microinvasive disease, frozen section examination fails to detect the area of invasion but reliably detects clear resection margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
10
0
Order By: Relevance
“…In fact, incomplete excision of CIN may result in a significant problem when opting for colposcopic follow-up on an outpatient basis, since patients living far from healthcare centers are often unable to comply with scheduled visits, which ultimately facilitates progression of the disease to more advanced stages [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, incomplete excision of CIN may result in a significant problem when opting for colposcopic follow-up on an outpatient basis, since patients living far from healthcare centers are often unable to comply with scheduled visits, which ultimately facilitates progression of the disease to more advanced stages [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al [11] evaluated patients submitted to cone/frozen section examination followed by hysterectomy and reported that the depth of the cone ranged from 1 to 2.5 cm, with 64% of positive margins. Of these, residual disease was found in the uterus in 68.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, since a discrepancy may no longer be detectable on inaccurate therapy, most gynecologists and pathologists do not agree with applying FSE after CKC (Cold Knife Conization). Carvalho et al diagnosed two cases of microinvasive carcinoma as CIN with less than 2 mm stromal invasion by FSE (8). In the study by Hasanzadeh et al (7) the discrepancy rate was 25% (5:20), where FSE revealed CIN 3 in one patient, whereas paraffin section showed invasive carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The role of FS examinaion (FSE) in CIN has not received much attention. Some researchers have discussed high concordance with the definitive paraffin examination in grading the lesion, but there are few studies evaluating the role of FSE of resection margin status (7)(8)(9). In addition, there are conflicting reports on the efficiency of FSE of the cone specimen in evaluating the margin status.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of this approach have all been from academic centers in the United States [4, 7, 8] and other countries [5, 6, 9], and presumably pathologists at academic centers had extra training or interest in gynecologic malignancies. At MD Anderson Cancer Center, all specimens were reviewed by 1 of 6 pathologists subspecialized in the area of gynecologic pathology and therefore spend the majority of their time reviewing gynecology cases.…”
Section: Discussionmentioning
confidence: 99%